Effect of Salt, Nutrients, and Native Microbe Additions on Common Dune Restoration Grasses - Clark, G. Scott; Busch, Michelle H.; Crawford, Kerri M. (Journal of coastal research, 2021)
Clark, G.S.; Busch, M.H., and Crawford, K.M., 2021. Effect of salt, nutrients, and native microbe additions on common dune restoration grasses. Journal of Coastal Research, 37(5), 1025–1034. Coconut Creek (Florida), ISSN 0749-0208. Sand dunes are a valuable resource that shelters coastal communities and wildlife. Unfortunately, their survival is threatened by commercial development and erosion accelerated by climate change. Restoring sand dunes is challenging because of the difficulty in establishing vegetation in such a hostile environment. Restoration practitioners have responded by choosing stress-tolerant native species, adding nutrients, or incorporating native microbial communities into transplanted soils, but little is known about how these practices interact. In other systems, native microbes sometimes increase plant performance and salt tolerance. Nutrient additions promote growth but may inhibit development of beneficial fungi and disproportionately benefit some plant species at the expense of community diversity. To explore these interactions, two grasses commonly used in dune restorations—Panicum amarum and Uniola paniculata—were grown in a greenhouse and exposed to soil with and without native microbiota and to a range of nutrient and salinity treatments. Native microbial additions had little impact on live, aboveground biomass or the salt tolerance of the nursery-grown plants. Nutrient additions did not inhibit beneficial fungi. In fact, the density of extraradical hyphae in the soil increased by an average of 31% across all plants subject to a balanced, slow-release fertilizer. The two grasses responded differently to the salinity and nutrient treatments. Under a 2.5% salinity treatment, average live aboveground biomass for P. amarum fell 52%, compared with a 5.5% increase for U. paniculata. None of the nutrient additions affected U. paniculata; however, a combination of nitrogen and phosphorus increased P. amarum live, aboveground biomass by 356%. The strong response of P. amarum to fertilization offers a path to rapid growth of dune vegetation, but it may foster that species' dominance, which could lower the plant community's aggregate resistance to salinity.